The Representation of Sita and Rama in Cok Sawitri’s Sitayana: A Critical Discourse Analysis - Liana Shinta Dewi; Winasti Rahma Diani (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
The aim of this research is to reveal the representation of Sita and Rama in the novel Sitayana. This research uses Norman Fairclough’s critical discourse analysis as both theory and method. Data collection and data analysis conducted through text analysis, discourse practice analysis, and social practice analysis. The results show that, at textual level, there is a different constructions of Sita and Rama from their classical form. The representation of Rama is weakened meanwhile the representation of Sita is strengthened. This construction is shaped by various overlapping discourses and ideological contestations within the text. The contested ideology in Sitayana are feminism, patriarchy, traditionalism, modernism, capitalism, and feudalism. The novel offers an alternative reading of the Ramayana narrative that tend to differ from other interpretation of Ramayana. Sitayana provides an intersacting space between Rama dan Sita namely a shared position as victim. So that, Rama and Sita’s are not really in a black and white opposition.